The corporate imagination : how big companies make mistakes - Earl, Peter E. (Armonk, N.Y. : M.E. Sharpe ; Brighton, Sussex : Wheatsheaf Books, 1984)
The book has been written for practicing managers and for academic scholars and students of industrial and management economics.; but anyone interested in current policy debates about the future of modern-day capitalism should find that the book has something to offer.
Includes index.
Includes bibliographical references (p. 216-227.)
opc 27/09/16
Loans
Keywords: Organizational change; Organizational behavior; Business planning; Corporate planning